2011
DOI: 10.1007/s10549-011-1888-1
|View full text |Cite
|
Sign up to set email alerts
|

Global and focal brain volume in long-term breast cancer survivors exposed to adjuvant chemotherapy

Abstract: A limited number of studies have associated adjuvant chemotherapy with structural brain changes. These studies had small sample sizes and were conducted shortly after cessation of chemotherapy. Results of these studies indicate local gray matter volume decrease and an increase in white matter lesions. Up till now, it is unclear if non-CNS chemotherapy is associated with long-term structural brain changes. We compared focal and total brain volume (TBV) of a large set of non-CNS directed chemotherapy-exposed bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
113
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 25 publications
(50 reference statements)
7
113
1
3
Order By: Relevance
“…Consistent with this explanation was that the median time since completion of chemotherapy was approximately 55 months for our participants at the time of neuropsychological testing, whereas assessments of cognitive function in other studies took place sooner after chemotherapy completion [7,8,16]. However, such an explanation does not simply rule out future cognitive impairment as previous studies also showed chemotherapy to be associated with cognitive impairment approximately 10 years later [10] and reductions in total brain volume and overall gray matter volume approximately 20 years later [13]. Clearly, longitudinal studies with a baseline neuropsychological examination before initiation of chemotherapy and neuropsychological examinations on both the shorter and longer term after completion of chemotherapy are needed in order to precisely locate the time window(s) when cognitive impairment occurs.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Consistent with this explanation was that the median time since completion of chemotherapy was approximately 55 months for our participants at the time of neuropsychological testing, whereas assessments of cognitive function in other studies took place sooner after chemotherapy completion [7,8,16]. However, such an explanation does not simply rule out future cognitive impairment as previous studies also showed chemotherapy to be associated with cognitive impairment approximately 10 years later [10] and reductions in total brain volume and overall gray matter volume approximately 20 years later [13]. Clearly, longitudinal studies with a baseline neuropsychological examination before initiation of chemotherapy and neuropsychological examinations on both the shorter and longer term after completion of chemotherapy are needed in order to precisely locate the time window(s) when cognitive impairment occurs.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, from a neuro-epidemiological perspective, it is important to examine whether treatment with chemotherapy in (late) adulthood accelerates cognitive decline and increases the risk of dementia. A previous study of breast cancer patients showed that treatment with chemotherapy was associated with reductions in overall gray matter volume about 20 years later [13].…”
mentioning
confidence: 99%
“…Examinations of cortical structure using magnetic resonance imaging (MRI) have demonstrated reductions of both gray and white matter volume when comparing chemotherapy-treated patients with either healthy controls [25] or untreated patients [26]. Prospective studies have revealed that both frontal and temporal cortex showed the most pronounced volume reductions [27,28].…”
Section: Manymentioning
confidence: 99%
“…The exact mechanisms of this dysfunction remain unclear, although there is emerging evidence that chemotherapy may accelerate cognitive and brain aging. For example, one study noted that gray matter atrophy in chemotherapy-treated (C+) BC survivors was comparable to the effect of 4 y of additional aging (3). Additionally, a previous epidemiological study demonstrated that C+ BC survivors were at higher risk for dementia than nonchemotherapy-treated survivors (C−) (4).…”
mentioning
confidence: 99%